2009
DOI: 10.1128/jb.00292-09
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Novel Alleles of the Escherichia coli umuDC Genes Identifies Additional Interaction Sites of UmuC with the Beta Clamp

Abstract: Translesion synthesis is a DNA damage tolerance mechanism by which damaged DNA in a cell can be replicated by specialized DNA polymerases without being repaired. The Escherichia coli umuDC gene products, UmuC and the cleaved form of UmuD, UmuD, comprise a specialized, potentially mutagenic translesion DNA polymerase, polymerase V (UmuD 2 C). The full-length UmuD protein, together with UmuC, plays a role in a primitive DNA damage checkpoint by decreasing the rate of DNA synthesis. It has been proposed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…We observed that strains expressing UmuC S31A had a growth defect and subsequently identified populations of strains expressing UmuC S31A with severe, intermediate, or no growth defects, indicating that this variant acquired suppressor mutations. Strains expressing UmuC S31L did not have this growth defect (5). The location and behavior of S31A as well as those of S31L suggest that this residue plays an important role in UmuC function and perhaps, more specifically, in template DNA alignment in the active site.…”
Section: Discussionmentioning
confidence: 88%
“…We observed that strains expressing UmuC S31A had a growth defect and subsequently identified populations of strains expressing UmuC S31A with severe, intermediate, or no growth defects, indicating that this variant acquired suppressor mutations. Strains expressing UmuC S31L did not have this growth defect (5). The location and behavior of S31A as well as those of S31L suggest that this residue plays an important role in UmuC function and perhaps, more specifically, in template DNA alignment in the active site.…”
Section: Discussionmentioning
confidence: 88%
“…The roles of the E. coli ␤ clamp in translesion synthesis are well established (5,8,30,31). Binding sites on the E. coli ␤ clamp that accommodate translesion polymerases pol IV (DinB) and pol V (UmuD 2 ЈC) have been identified, and the consequence of disrupting their association with the ␤ clamp has illustrated the critical importance of the ␤ clamp to the activity of both of these polymerases (4,5,8,26,30,31,48,49).In addition to the involvement of the ␤ clamp in replication initiation, DNA replication, and translesion synthesis, the E. coli and B. subtilis ␤ clamp also functions in DNA mismatch repair (MMR) (45,46,64). The MMR pathway recognizes and repairs DNA polymerase errors, contributing to the overall fidelity of the DNA replication pathway (reviewed in references 42 and 60).…”
mentioning
confidence: 99%
“…The roles of the E. coli ␤ clamp in translesion synthesis are well established (5,8,30,31). Binding sites on the E. coli ␤ clamp that accommodate translesion polymerases pol IV (DinB) and pol V (UmuD 2 ЈC) have been identified, and the consequence of disrupting their association with the ␤ clamp has illustrated the critical importance of the ␤ clamp to the activity of both of these polymerases (4,5,8,26,30,31,48,49).…”
mentioning
confidence: 99%
“…The operator sequences of pGY9739 and pGY9738 contain the o 1 c mutation where a single base substitution leads to modestly increased expression of umuD and umuC (28,29). Strains were grown in Luria broth at 37°C supplemented with spectinomycin (60 g/ml) or ampicillin (100 g/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Expression of UmuD and UmuDЈ proteins were accomplished as previously described (31). Cells were harvested, and UmuD and UmuDЈ proteins were purified according to published methods (28). The ␤ clamp was also purified using the method published for UmuD and UmuDЈ.…”
Section: Methodsmentioning
confidence: 99%